KYIV ADDRESSES OF VOLODYMYR PRAVDYCH-NEMINSKI (City: History, Culture, Society, 2021)
Biography of Ukrainian neuroscientist and physiologist Volodymyr Pravdych-Neminski (1878-1952) is not known well despite his pioneering research on mammal electroencephalography. Historiographic review shows the low interest of previous researchers in his private life history as his detainment, exile and forecoming repressions by Soviet state security organs made this topic dangerous. In this study, the widest to date material on his Kyiv period of life was collected and analyzed. Historical addresses in Kyiv connected to Pravdych-Neminski are described: his parents’ real estate, rented and office accommodations, working and teaching institutions.  His closest relatives were parents Volodymyr and Anna, uncle Nicolas, brother Pavlo. Some unknown facts of his private life are uncovered, i.e. his marriage in 1906 or 1907 with Oleksandra Ludvigivna, secret marriage and death of his second daughter, everyday life details. This work also shows Pravdych-Neminsky close circle in Kyiv Polytechnics and Ukrainian Academy of Sciences. Newly found and studied the archived criminal case of 1929 is an important source of historical data for Pravdych-Neminski life story. Together these findings improve our knowledge of his biography. It is highly important to preserve the historical memory of this prominent Kyiv citizen and researcher.
Keywords: history of science; Kyiv; Volodymyr Pravdych-Neminski; Kyiv addresses; repressed scientists; neurobiologists; biographies